2013
DOI: 10.1007/s00382-013-1676-1
|View full text |Cite
|
Sign up to set email alerts
|

The Indo-Australian monsoon and its relationship to ENSO and IOD in reanalysis data and the CMIP3/CMIP5 simulations

Abstract: A large spread exists in both Indian and Australian average monsoon rainfall and in their interannual variations diagnosed from various observational and reanalysis products. While the multi model mean monsoon rainfall from 59 models taking part in the Coupled Model Intercomparison Project (CMIP3 and CMIP5) fall within the observational uncertainty, considerable model spread exists. Rainfall seasonality is consistent across observations and reanalyses, but most CMIP models produce either a too peaked or a too … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
168
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(184 citation statements)
references
References 105 publications
(80 reference statements)
15
168
0
1
Order By: Relevance
“…This study found that offshore microplastics, introduced to the study site with the Leeuwin current, increased with strength of flow in May. Both the ITC and Australian Monsoon driving LC variability are susceptible to changes based on El Niño Southern Oscillation (ENSO) (Pearce and Phillips, 1988;Jourdain et al, 2013). Therefore, concentrations may be significantly higher during non-ENSO years and La Nina episodes (Pearce and Phillips, 1988).…”
Section: Concentrations and Drivers Of Variabilitymentioning
confidence: 85%
“…This study found that offshore microplastics, introduced to the study site with the Leeuwin current, increased with strength of flow in May. Both the ITC and Australian Monsoon driving LC variability are susceptible to changes based on El Niño Southern Oscillation (ENSO) (Pearce and Phillips, 1988;Jourdain et al, 2013). Therefore, concentrations may be significantly higher during non-ENSO years and La Nina episodes (Pearce and Phillips, 1988).…”
Section: Concentrations and Drivers Of Variabilitymentioning
confidence: 85%
“…In particular, the Coupled Model Intercomparison Project phase 5 (CMIP5) simulations are used in the Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report for future climate projection (Flato et al 2013). However, the ability of GCMs to simulate the mean climate and climate variability over the Maritime Continent remains a modeling challenge (Jourdain et al 2013). As one of the main diabatic heat sources for regional and global circulation, biases in the mean state simulations of the Maritime Continent also affect tropical and extratropical variability and teleconnections (Neale and Slingo 2003;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the fidelity of CMIP5 models in simulating the Australian monsoon (Jourdain et al 2013;Ackerley et al 2014), the western Pacific monsoon (Brown et al 2013) and the Asian summer monsoon (Sperber et al 2013). These studies found that different models show varying ability at each aspect of monsoon simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the nature of the ENSO-ISM relationship and specifically constraining the dynamics that have generated the recent change in the coupling between the systems is a problem ideally suited for general circulation models (GCMs) (e.g., Jourdain et al, 2013) where the response of the systems to various forcing mechanisms could be tested. However, systematic errors in simulating the mean state and variability of both ENSO and the ISM systems have hampered the ability to utilize this tool (Annamalai et al, 2007;Collins et al, 2010).…”
Section: Introductionmentioning
confidence: 99%